Identifikasi Bentuk-Bentuk Ketidaksesuaian Tata Ruang di Dalam Kawasan Teluk Youtefa Kota Jayapura - Mayor, Bryan Samuel; Andri Kurniawan; Lutfi Muta'ali (Geography Education Study Program, Universitas Kanjuruhan Malang, 2025)
Spatial deviation in Youtefa Bay Area, Jayapura City, which has the status of Natural Tourism Park (TWA) and Protected Forest (HL), is the main problem due to land conversion in the urban center. This research aims to identify the form of non-conformity of spatial utilization in the area. A quantitative approach was used with methods of analyzing Maxar Technologies 2025 satellite imagery, overlaying land use maps with RTRW No. 1/2014, and expert judgment validation. The results show that out of 480.36 hectares, 38.68 hectares are spatially incompatible, mainly for trade and services (13.77 hectares) and settlements (8.13 hectares). These non-conformities were analyzed using the DPSIR (Driver, Presure, State, Impact and Response) method, which reveals the dynamics of regional development such as urbanization, mangrove land exploitation, ecosystem degradation, and flood risk as causal factors causing the main deviations. This research recommends strengthening urbanization control through development regulations, prohibiting customary land transactions that violate the RTRW, rehabilitating mangrove ecosystems, and coordinating across agencies to enforce spatial regulations to maintain environmental sustainability.